Antidiabetic and antihyperlipidemic activity of hydroalcoholic extract of Withania coagulans Dunal dried fruit in experimental rat models - Ankur Datta (Journal of Ayurveda and Integrative Medicine, 2013)
Objective: Evaluation of antidiabetic potential of the hydroalcoholic extract of Withania coagulans Dunal dried fruit (WCDF) alone and in combination with glipizide, in streptozotocin-induced diabetes, and evaluation of possible antihyperlipidemic activity of the same extract in high-cholesterol diet-induced hyperlipidemia, in albino rats. Materials and Methods: Experimental diabetes was induced in 30 albino rats with intraperitoneal injection of streptozotocin (55 mg/kg). The rats were divided into five groups receiving the following treatments orally for 4 weeks: Vehicle, glipizide (2.5 mg/kg), WCDF extract (1000 mg/kg), WCDF extract (1000 mg/kg) plus glipizide (1 mg/kg) and WCDF extract (1000 mg/kg) plus0 glipizide (2.5 mg/kg). Fasting and postprandial blood glucose levels were measured every week for 4 weeks. Endocrine pancreas histopathology was done at the end. In a separate set of experiment, five groups of six albino rats each, received orally for 4 weeks, vehicle, cholesterol (25 mg/kg/day), cholesterol (25 mg/kg/day) plus atorvastatin (7.2 mg/kg/day), cholesterol (25 mg/kg/day) plus WCDF extract (1000 mg/kg/day) and no treatment, respectively. Estimation of serum lipid profile and liver histopathology was done at the end of 4 weeks. Statistical Analysis: Between-group and within-group comparisons were respectively done by analysis of variance (ANOVA) and repeated measures ANOVA, followed by post hoc Tukey′s test, with a significance level of P < 0.05. Results and Conclusions: The 4-week treatment with WCDF extract significantly reversed hyperglycemia in streptozotocin-induced diabetes that was comparable to glipizide. When combined with glipizide (2.5 mg/kg), WCDF extract produced a synergistic antihyperglycemic effect as well as improvement in pancreatic histopathology. Moreover, hydroalcoholic extract of WCDF was effective and comparable to atorvastatin in controlling the high-cholesterol diet-induced hyperlipidemia in rats.